2018
DOI: 10.1007/s12070-018-1344-1
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Neuroendocrine Carcinoma: A Rare Nasopharyngeal Malignancy with Aggressive Clinical Course

Abstract: Primary small cell neuroendocrine carcinoma is uncommon in head and neck region, with occasional cases in nasopharynx. Distinction from other round cell tumors is imperative to ensure optimal patient management. We present a case of a 30-year-old woman who presented with a rapidly growing nasopharyngeal mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…However, the patient eventually died of liver failure caused by further multiple liver metastases. The OS of the patient is about 18 months, which is at an intermediate level among the current literature results [3][4][5][6][7][8][9][10] . According to the literature retrieved so far, nasopharyngeal neuroendocrine carcinoma has the risk of central nervous system metastasis, and it is necessary to carry out prophylactic cranial irradiation [11] .…”
Section: Discussionmentioning
confidence: 89%
“…However, the patient eventually died of liver failure caused by further multiple liver metastases. The OS of the patient is about 18 months, which is at an intermediate level among the current literature results [3][4][5][6][7][8][9][10] . According to the literature retrieved so far, nasopharyngeal neuroendocrine carcinoma has the risk of central nervous system metastasis, and it is necessary to carry out prophylactic cranial irradiation [11] .…”
Section: Discussionmentioning
confidence: 89%
“… 2 Nevertheless, the prognosis of nasopharyngeal small cell carcinoma (SmCC), which is a relatively rare type of nasopharyngeal cancer, remains poor. 3 A population-based analysis of the National Cancer Database revealed that only .3% of all head and neck cancer patients were diagnosed as having SmCC, among which 10% were nasopharyngeal in origin. 4 Moreover, nasopharyngeal SmCC has been reported to have the worst prognosis of all SmCCs of the head and neck.…”
Section: Introductionmentioning
confidence: 99%
“…Current strategies for the therapeutic treatment of nasopharyngeal SmCC comprise chemotherapy and/or radiotherapy; surgery can also serve as a therapeutic modality for early stage nasopharyngeal SmCC. 20 - 24 Unfortunately, there are few available studies in this regard. Various therapies, including surgery, radiotherapy, chemotherapy, immune therapy, and combined therapies, 5 , 21 , 25 , 26 have been studied for SmCCs of the head and neck.…”
Section: Introductionmentioning
confidence: 99%
“…They usually appear in the sixth or seventh decade of life and carry a poor prognosis 4,5 . Distinction from other conventional nasopharyngeal malignancies can represent a diagnostic challenge as a result of various morphological characteristics that can mimic other small round blue cell tumours, such as neuroblastomas, lymphomas, primitive neuroectodermal tumours, Ewing sarcoma, desmoplastic round cell tumours, NUT midline carcinomas, adenoid cystic carcinomas and basaloid carcinomas 6 . NECs of the nasopharynx can be divided into large cell neuroendocrine carcinoma (LNEC) and small cell neuroendocrine carcinoma (SNEC) 6,7 .…”
Section: Introductionmentioning
confidence: 99%